The Vulnerability of Qilian Juniper to Extreme Drought Events - Wang, Xiaofeng; Yang, Bao; Ljungqvist, Fredrik Charpentier (Frontiers in Plant Science, 2019)
Identifying which trees are more vulnerable to extreme climatic events is a challenging problem in our understanding of forest and even ecosystem dynamics under climate change scenarios. As one of the most widely distributed tree species across the arid and semi‐arid northeastern Tibetan Plateau, Qilian juniper (Juniperus przewalskii Kom.) is the main component of the local forest ecosystem, providing critical insurance for the ecological security of the surrounding areas. However, this species’ ability to cope with climate extremes (especially drought) has not been adequately assessed. Here, we apply a dendro-ecological approach which considers indices of resistance and resilience to quantify the vulnerability of Qilian junipers to the extreme drought events of 1957, 1966, 1979, and 1995. A total of 532 Qilian juniper trees from different age stages (100–1100 years) and altitudes (3500–4000 m a.s.l.) were studied to assess their response characteristics during these four drought extremes. We conclude that drought extremes have a significant negative impact on the growth of Qilian juniper. The oldest Qilian junipers at the lower altitudes constituted the most vulnerable populations across the northeastern Tibetan Plateau and were characterized by the lowest resistance values, narrowest annual rings and the highest proportion of missing rings during the four drought years. Tree resilience after droughts was strongly related to the intensity of the drought event and did not change with tree age or elevation. A threshold of tree tolerance to drought may exist, with the more vulnerable tree individuals (e.g., the oldest Qilian junipers from lower altitudes) being exposed to the highest mortality risk when drought intensity exceeds the threshold value. Such a threshold needs further consideration, through the study of trees that have died (or are about to die) due to extreme droughts.